PERAN WIRID DALAM MEMPERKUAT KOHESI SOSIAL: STUDI KASUS DI JORONG DATA SUNGAI PUAR NAGARI SUNGAI PUAR KECAMATAN PALEMBAYAN KABUPATEN AGAM - Julmi Sinta Mustafa; Abdul Gaffar; Noor Fadli Marh; Tyka Rahman (CV. ADIBA AISHA AMIRA, 2025)
Wirid plays a role in strengthening social cohesion in Jorong Data Sungai Puar, Nagari Sungai Puar, Palembayan District, Agam Regency. As part of routine religious activities, wirid is believed to have a positive impact on strengthening social relations between residents. This research adopts a qualitative approach with a case study method, which involves collecting data through interviews, observation and documentation. Research findings indicate that wirid activities carried out collectively not only strengthen spiritual ties between community members, but also increase the sense of togetherness and social solidarity in the environment. Wirid functions as a medium for instilling the values ​​of mutual cooperation, mutual support, and creating a safe and comfortable atmosphere in social life. Therefore, the practice of wirid has an important role in strengthening social cohesion in Jorong Data Sungai Puar and contributing to the creation of harmony in the local community